Updates on Preprocedural Evaluation and Patient Selection for Prostatic Artery Embolization - Rostambeigi, Nassir; Golzarian, Jafar; Little, Mark W. (Seminars in Interventional Radiology, 2022)
Prostatic artery embolization (PAE) is a safe and effective treatment for benign prostatic hyperplasia. Patient evaluation is a critical and important part of this growing practice. History taking should include symptoms score evaluations for lower urinary tract symptoms, erectile function, and prostatitis symptoms score. The objective evaluations commonly include measurement of prostate specific antigen, postvoid residual volume, and uroflowmetry as well as urodynamic studies in selective patients. Imaging evaluation may include computed tomography angiography or magnetic resonance angiography, elucidating prostate volume, prostate gland morphology, vasculature, and prostate cancer. With evolving knowledge on PAE, we aim to discuss patient evaluation and selection based on updated evidence and discuss specific scenarios.
Keywords: prostate; embolization; benign prostatic hypertrophy; prostatic artery embolization; lower urinary tract symptoms; imaging; interventional radiology